Comparing models of counterproductive workplace behaviors: The Five-Factor Model and the Dark Triad - DeShong, Hilary L; Grant, DeMond M; Mullins-Sweatt, Stephanie N (Personality and individual differences, 2015)
Highlights•Examined best personality model to describe counterproductive workplace behaviors. •Five Factor Model predicted counterproductive work behaviors better than Dark Triad. •Agreeableness and conscientiousness provide the most parsimonious model.